Inverted perovskite solar cells with enhanced lifetime and thermal stability enabled by a metallic tantalum disulfide buffer layer. Issue 11 (16th April 2021) - Chatzimanolis, Konstantinos; Rogdakis, Konstantinos; Tsikritzis, Dimitris; Tzoganakis, Nikolaos; Tountas, Marinos; Krassas, Miron; Bellani, Sebastiano; Najafi, Leyla; Martín-García, Beatriz; Oropesa-Nuñez, Reinier; Prato, Mirko; Bianca, Gabriele; et al.
Abstract : An ultra-thin 2D TaS2 buffer layer on top of the electron transport layer improves the efficiency, the lifetime and the thermal stability of inverted perovskite solar cells. Abstract : Perovskite solar cells (PSCs) have proved their potential for delivering high power conversion efficiencies (PCE) alongside low fabrication cost and high versatility. The stability and the PCE of PSCs can readily be improved by implementing engineering approaches that entail the incorporation of two-dimensional (2D) materials across the device's layered configuration. In this work, two-dimensional (2D) 6R-TaS2 flakes were exfoliated and incorporated as a buffer layer in inverted PSCs, enhancing the device's PCE, lifetime and thermal stability. A thin buffer layer of 6R-TaS2 flakes was formed on top of the electron transport layer to facilitate electron extraction, thus improving the overall device performance. The optimized devices reach a PCE of 18.45%, representing a 12% improvement compared to the reference cell. The lifetime stability measurements of the devices under ISOS-L2, ISOS-D1, ISOS-D1I and ISOS-D2I protocols revealed that the TaS2 buffer layer retards the intrinsic, thermally activated degradation processes of the PSCs. Notably, the devices retain more than the 80% of their initial PCE over 330 h under continuous 1 Sun illumination at 65 °C.